A review on mid-band and high-band 5G MIMO antenna designs: challenges and research directions - Upali Aparajita Dash; Arun Agarwal; Sasmita Pahadsingh (EURASIP Journal on Wireless Communications and Networking)
Abstract Modern wireless communication demands 5G-enabled systems capable of handling high data rate and channel bandwidth. Recently, circular-polarized multiple-input–multiple-output technology in the user equipment has dragged attention of the designers. Antenna design involves complex mathematical formulations and assumptions of geometrical variables of structure and feeding methods. This task makes antenna design rigorous and time intensive. The authors have attempted to initialize design parameters that include, number and positioning of ports, shape and position of dielectric resonator antennas, usage of metasurface walls to attain high isolation, band width, gain, and efficiency. Scopus-indexed research papers have been carefully selected and reviewed to achieve the aforementioned purpose. Research papers on planar, dielectric resonator, circularly polarized dielectric resonators and metasurface-incorporated antennas have been organized and compared in different segments. The review may help in providing a definite direction of designing a MIMO antenna for either mid-band or high-band 5G communications.